Teaching Functional Text Using Know-Want-Learned Strategy - Khairul Fajri (Research in English and Education Journal, 2018)
The objective of this research is to find out about the implementation of KWL strategy to improve students’ comprehension in functional text of class VIII4 at MTsN 4 Banda Aceh. The sample was taken randomly of the students of class VIII. The data for this study were obtained by using test namely pretest and posttest as the instrument for collecting the data. The text used in the tests was functional texts in the form of invitation. The tests consisted of 5 essay questions that covers the structure of text and detail information. In analyzing the data, the writer used statistical formula suggested by Ary, et al (2010). The research finding shows that there was  a significant improvement in the students’ reading ability after they learnt with KWL strategy. It is proven with the mean score of pretest (61.9) and the mean score of posttest (78.06). The gap from the mean of pretest and posttest was 16.12. It showed that there was improvement in student score. The improvement also can be seen from the students who passed the minimum passing grade. The minimum passing grade of the school is 75. After the posttest there were 22 out of 31 students have successfully passed the passing grade. In hypothesis testing the researcher did the calculation to get t-test score to do the hypothesis testing. The T-test score revealed that (t-score=3.83 t-table=2.04) which mean alternative hypothesis was accepted and null hypothesis rejected. As a result KWL strategy is effective in improving student comprehension. The students also become more focus in finding specific information from the functional text.